2020
DOI: 10.18388/abp.2020_5080
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of single nucleotide polymorphisms identified through the use of SNP assay in Romanian and Chinese Holstein and Simmental cattle breeds

Abstract: Simmental and Holstein cattle, being among the most widely distributed breeds worldwide, have been subjected to continuous selection for distinct purposes. In the current study, we evaluated the levels of SNPs identified through the use of SNP assay in Romanian Holstein and Romanian Simmental cattle, which then were compared to the data from Chinese Holstein and Chinese Simmental cattle. In total, 282 animals were genotyped: Romanian Holstein (n=30), Romanian Simmental (n=22), Chinese Holstein (n=96) and Chine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…The basic genetic diversity indices (H o , H e , and MAF) pointed to the increase of overall genomic homozygosity in each analysed population consistent with Matukumalli et al [75], which developed and characterised the high-density bovine SNP microarray. Similarly, various other genomic studies reported the decrease of overall heterozygosity in European cattle breeds [6,70,76,77]. Heterozygosity can range from 0 (no heterozygosity) to 1 (populations with a large number of alleles with approximately the same frequency).…”
Section: Discussionmentioning
confidence: 71%
“…The basic genetic diversity indices (H o , H e , and MAF) pointed to the increase of overall genomic homozygosity in each analysed population consistent with Matukumalli et al [75], which developed and characterised the high-density bovine SNP microarray. Similarly, various other genomic studies reported the decrease of overall heterozygosity in European cattle breeds [6,70,76,77]. Heterozygosity can range from 0 (no heterozygosity) to 1 (populations with a large number of alleles with approximately the same frequency).…”
Section: Discussionmentioning
confidence: 71%
“…In total, 20 lactating adult multiparous cows of the Romanian Holstein breed were tested between August and September 2022. The Romanian Holstein breed (RH, national name Bălțată cu Negru Românească) belongs to the dairy Holstein-Friesian strain, with a current census of 264,000 cows, representing 22% of the breed structure in Romania ( 36 ). The RH originates in the 19th century, being the result of systematic crossbreeding between Friesian bulls imported from Denmark and Germany and local cattle, such as Romanian Spotted and Dobruja Red.…”
Section: Methodsmentioning
confidence: 99%
“…The α value was not fixed for each phenotype or even different functional regions of the genome [ 11 ]. A value of α = 0 or −1 is usually used to estimate the functional enrichment in livestock population [ 12 ], but the consequences of different α values on heritability enrichment have not been systematically compared and studied.…”
Section: Introductionmentioning
confidence: 99%